Remembering the Holocaust in Germany, Austria, Italy and Israel : "Vergangenheitsbewältigung" as a historical quest - Pinto, Vincenzo (2022)
"Remembering the Holocaust in Germany, Austria, Italy and Israel: "Vergangenheitsbewältigung" as a Historical Quest offers an account on post-war coming-to-terms with the Holocaust tragedy in some European countries, such as Germany, Austria, and Italy. The subject has attracted more attention in recent years, since the long transition to liberal democracy seems to have put an end to the main theme of the memory of the Second World War. The main point of the volume is the making of a new generational memory after the "end of history". What is to be done after the making of a globalised world? What about the memorialisation of the last century?